Alpha-synuclein modulates NR2B-containing NMDA receptors and decreases their levels after rotenone exposure. (June 2015) - Navarria, Laura; Zaltieri, Michela; Longhena, Francesca; Spillantini, Maria Grazia; Missale, Cristina; Spano, PierFranco; Bellucci, Arianna
Highlights: Wild type and C-terminally truncated α-syn can interact with NR2B-containing NMDAR. Alpha-synuclein negatively modulates NR2B-containing NMDAR activation. Alpha-synuclein protects neurons from rotenone toxicity by reducing NR2B levels. Abstract: Alpha-synuclein (α-syn) is the main protein component of Lewy bodies (LBs), that together with nigrostriatal dopamine neuron loss constitute typical pathological hallmarks of Parkinson's disease (PD). Glutamate N -methyl-d-aspartate receptor (NMDAR) abnormalities, peculiarly involving NR2B-containing NMDAR, have been observed in the brain of PD patients and in several experimental models of the disease. Recent findings, indicating that α-syn can modulate NMDAR trafficking and function, suggest that this protein may be a pivotal regulator of NMDAR activity. Prompted by these evidences, we used fluorescence immunocytochemistry, western blotting and ratiometric Ca 2+ measurements to investigate whether wild type (wt) or C-terminally truncated α-syn can specifically modulate NR2B-containing NMDAR levels, subcellular trafficking and function. In addition, we evaluated whether the exposure of primary cortical neurons to increasing concentrations of rotenone could differentially regulate NR2B levels and cell viability in the presence or in the absence of α-syn. Our results indicate that both wt and C-terminally truncated α-syn negatively modulate NR2B-containing NMDAR levels, membrane translocation and function. Moreover, we found that absence of α-syn abolishes the rotenone-dependent decrease of NR2B levels and reduces neuronal vulnerability in primary cortical neurons. These findings suggest that α-syn can modulate neuronal resilience by regulating NR2B-containing NMDAR, whose specific alterations could connect α-syn pathology to neuronal degeneration in PD.